ANALISIS KEBUTUHAN PETUGAS REKAM MEDIS PASCA IMPLEMENTASI REKAM MEDIS ELEKTRONIK (RME) MENGGUNAKAN METODE ABK-KES DI RSUD TOTO KABILA TAHUN 2025 - Putri Rahmawati Sujitno; Merlin Abd Rahman; Moh Ichsan Arifin Antu (PRIMA WIYATA HEALTH, 2025)
Background: The Health Workload Analysis (ABK-Kes) method is a standardized approach used to calculate the need for healthcare personnel based on actual workloads in each functional unit. Following the implementation of the Electronic Medical Record (EMR) system at RSUD Toto Kabila, several disparities in workload distribution were observed, with some staff, particularly in the analysis unit, assigned overlapping tasks. This condition led to inefficiencies and an imbalance in human resource deployment. Objectives: This study aimed to analyze the ideal number of medical record personnel required after the implementation of the Electronic Medical Record (EMR) system at RSUD Toto Kabila in 2025 using the Health Workload Analysis (ABK-Kes) method, in order to ensure optimal human resource distribution and workload efficiency. Methods: This research employed a quantitative descriptive design. All medical record officers at RSUD Toto Kabila were included using total sampling. Data were collected through observation, structured interviews, stopwatch timing, and document review. The ABK-Kes method was applied to calculate workload volume, effective working time, and standard time per task in each unit. Results: The results indicated that the ideal staffing needs include 3 officers in outpatient registration, 2 in inpatient/ER registration, 4 in analysis, 5 in coding, 2 in filing, and 1 in reporting. Staffing shortages were identified in the inpatient registration and analysis units, while other units met or exceeded requirements. An imbalance in task distribution was found, especially in cases where one officer performed duties across multiple units. Conclusion: The implementation of the EMR system has created changes in workload distribution among medical record officers. The ABK-Kes method provides a structured basis for evaluating staffing needs. Periodic evaluation and strategic workforce planning are necessary to ensure balanced workloads and improved data accuracy in EMR management.